Imbibition of Swietenia macrophylla (Meliaceae) seeds: the role of stomata - Paiva, EAS; Lemos, J. P.; Oliveira, DMT (Oxford University Press, 2006)
Background and Aims the occurrence of stomata in seed coats is uncommon and there is limited information about their function(s). The aim of this study was to verify the distribution of stomata in seed coats of Swietenia macrophylla and to relate it to the imbibition process and aspects of the structure of the outer integument layers.Methods For the structural and ultrastructural studies, the seeds were processed using the usual techniques and studied under light and scanning electron microscopes. Histochemical tests were employed to identify the cell wall composition in the different seed coat portions. To assess the role of the stomata in the imbibition, non-impervious seeds were compared with partially impervious ones, in which only the embryo, median or hilar regions were left free. Further, the apoplastic pathway marker was employed to confirm the role of the stomata as sites of water passage during imbibition.Key Results A positive relationship was observed between seed coat thickness and stomata density. The stomata were devoid of movement, with a large pore. They occurred in large numbers in the embryo region and extended with lower frequency towards the wing. Imbibition rates were related to stomata density, suggesting that the stomata act as preferential sites for water entry in the S. macrophylla seeds.Conclusions At maturity, the stomata in the seed coat play a significant role in seed imbibition. The data may also infer that these permanently opened stomata have an important role in gas exchange during seed development, aiding embryo respiration.
Keywords: embryo; germination; integument; mahogany; Meliaceae; seed; seed anatomy; seed coat; seed imbibition; stomata; Swietenia macrophylla